Development of an in-house Lepto-LAT kit for screening and detection of Leptospira infection - Lan Anh, Le Thi; Thi Thuong, Vu; Thi Ha Giang, Pham; Thi Thanh Nga, Bui; Thi Hang, Minh; Phi Long, Trieu; Ha Thanh, Dao Thi; Van Anh, Le Thi; Huu Duc, Nguyen (Vietnam Journal of Biotechnology, 2021)
Leptospirosis is a common zoonotic disease in the tropics and subtropics. Leptospira infected human without prompt detection and treatment will face serious consequences such as acute hepatitis-kidneys, pulmonary hemorrhage which can lead to death. Besides the MAT gold standard method, Leptosipra antigens developed by DNA recombination technology have been widely studying and applying in diagnosis of Leptospira infection in human and animal. Overcoming the disadvantages of MAT and ELISA such as complicated protocol, which requires highly qualified staff and specialized equipment, the latex agglutination method has been studied and widely used in detecting pathogens such as Salmonella, E. coli, Leptospira in the world. The advantages of this method are simple operation, fast and cheap. In the previous article, we expressed Leptospira LigB antigen in E. coli cells and successfully purified it by affinity chromatography with 98% purity. In this paper, we present the process for establishment of a Lepto-LAT kit to detect Leptospira infection in dogs. This kit had the sensitivity and specificity of 91.75% and 91.57%, respectively.